Genome-wide identification of cyclin-dependent kinase (CDK) genes affecting adipocyte differentiation in cattle - Pan, Cuili; Lei, Zhaoxiong; Wang, Shuzhe; Wang, Xingping; Wei, Dawei; Cai, Xiaoyan; Luoreng, Zhuoma; Wang, Lei; Ma, Yun (BMC genomics, 2021)
Background Cyclin-dependent kinases (CDKs) are protein kinases regulating important cellular processes such as cell cycle and transcription. Many CDK genes also play a critical role during adipogenic differentiation, but the role of CDK gene family in regulating bovine adipocyte differentiation has not been studied. Therefore, the present study aims to characterize the CDK gene family in bovine and study their expression pattern during adipocyte differentiation. Results We performed a genome-wide analysis and identified a number of CDK genes in several bovine species. The CDK genes were classified into 8 subfamilies through phylogenetic analysis. We found that 25 bovine CDK genes were distributed in 16 different chromosomes. Collinearity analysis revealed that the CDK gene family in Bos taurus is homologous with Bos indicus , Hybrid-Bos taurus , Hybrid Bos indicus , Bos grunniens and Bubalus bubalis . Several CDK genes had higher expression levels in preadipocytes than in differentiated adipocytes, as shown by RNA-seq analysis and qPCR, suggesting a role in the growth of emerging lipid droplets. Conclusion In this research, 185 CDK genes were identified and grouped into eight distinct clades in Bovidae, showing extensively homology. Global expression analysis of different bovine tissues and specific expression analysis during adipocytes differentiation revealed CDK4 , CDK7 , CDK8 , CDK9 and CDK14 may be involved in bovine adipocyte differentiation. The results provide a basis for further study to determine the roles of CDK gene family in regulating adipocyte differentiation, which is beneficial for beef quality improvement.